The Position Medical Forensics and Visum Et Repertum in Adultery (Overspel) Cases in the Jenang Kutei Traditional Trial in Bengkulu, Indonesia - Emma Ellyani1, Khudzaifah Dimyati2, Absori2, Kelik Wardiono2, Sakroni1, Arief Budiono3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Proving is the action of presenting legally valid evidences by the Rajang Lebong customary judge to inspect cases of adultery (overspel), to achieve the truth according to the forensic science. This research uses a sosiological method with a descriptive-analysis approach regarding the forensics’ expert information and the position of visum et repertum in customary trials in the case of adultery. The aim of this research is to understand the real position of forensic experts and visum et repertum in the Rejang Lebong traditional trials. This research shows that the position of the forensics’ expert information of evidences and visum et repertum are accepted as proof in overspel cases.